The fundamentals ; v. 4 a testimony to truth (Los Angeles, CA The Bible Institute of Los Angeles, 1917)
Some articles include bibliographical references.
Originally published in 12 volumes. Algernon James Pollock, 1864-1957 (author of chapter 12), Brethren writer.
Keywords: Doctrine, theology